2016
DOI: 10.1680/jgein.16.00002
|View full text |Cite
|
Sign up to set email alerts
|

Field test of a geogrid-reinforced and floating pile-supported embankment

Abstract: A well-designed field experiment was carried out to enhance the understanding of a geogrid-reinforced and floating pile-supported (GRFPS) embankment constructed on alluvial soil with medium–low compressibility (ASMLC). Two test sections with identical reinforcement solutions and fill load were chosen for field monitoring which lasted approximately 32 months. The measurements, including pore water pressure, settlement, soil stress, strain in geogrid, and lateral displacement during and after the embankment fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The shear force l s F is calculated by Equation (3). Due to the symmetry of the laboratory test setup, it is sufficient to simulate only one section of the trapdoor test model.…”
Section: Dem Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The shear force l s F is calculated by Equation (3). Due to the symmetry of the laboratory test setup, it is sufficient to simulate only one section of the trapdoor test model.…”
Section: Dem Modelingmentioning
confidence: 99%
“…Piled embankments have been widely adopted to overcome intolerable total or differential settlements, large lateral displacements of highway, and railway engineering, especially for embankments constructed over soft soils [1][2][3][4][5][6][7][8][9]. Soil arching effect is a ubiquitous phenomenon occurred in the piled embankment to transfer the vertical stress from the relatively stiff pile to the softer soil due to the differential settlement [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [13] comparatively studied the long-term deformation of rockfill embankment under heavy loads through field creep test and numerical simulation, and the results are sensitive to the surrounding environment. Cao et al [14] designed a large field test and studied the deformation behaviours of embankment under the reinforcement of geogrids and supports of floating piles, but the test period is generally limited. The field test can observe the deformation behaviour of embankment, but the test period is lengthy and the test results are sensitive to environmental changes.…”
Section: State Of the Artmentioning
confidence: 99%
“…R. P. Chen [19] showed that substratum settlements account for a large proportion of the total settlement in an embankment, and the proportion of substratum settlement can be reduced by changing the pile length and, therefore, that the total settlement can be controlled. Cao [20] studied the reinforcement effect and the mechanism of pilesupported reinforcement technology in medium-low compressible soil and analyzed the deformation characteristics of foundation settlements and reinforced cushions. Zhang [21] studied the working behavior of pile-supported reinforced embankments in bridge head sections.…”
Section: Introductionmentioning
confidence: 99%